Sequence-based analysis of 5′UTR and coding regions of CASP3 in terms of miRSNPs and SNPs in targetting miRNAs. (June 2016) - Ergun, Sercan; Oztuzcu, Serdar
Graphical abstract: Polymorphisms in miRNA genes or miRNA target sites (miRSNPs) can change miRNA activity. Many researches have revealed that SNPs in miRNA target sites improve or decrease the efficacy of the interaction between miRNAs and their target genes. Cross-matches of SNPs in the miR-339-3p and in the binding site with 5′UTR of CASP3. Our aim was to specify miRSNPs on CASP3 gene (caspase-3) and SNPs in miRNA genes targeting 5′UTR and coding exons of CASP3, and evaluate the effect of these miRSNPs and SNPs of miRNA genes with respect to apoptosis. According to dbSNP 141 database, genomic locations of SNPs found in the miR-339-3p and in the binding site with 5′UTR of CASP3 were matched with each other. Co-localizations were screened. In the binding site, miR-339-3p makes 10 base-pairings with CASP3 5′UTR. MiR-339-3p geneomic sequence has three SNPs. Two of them (rs565188493, G/A; rs72631820, A/G) were localized in the binding site on the CASP3 5′UTR and one (rs373011663, C/T) was not on the binding site on the CASP3 5′UTR. Also, CASP3 5′UTR had a SNP (rs35372903, G/A) on binding site of miR-339-3p and this miRSNP and SNP (rs565188493, G/A) at miR-339-3p genomic sequence co-localized at the same genomic location of binding region. Therefore, this novel finding upon SNP cross-match between miR-339-3p and CASP3 5′UTR may give information about all these apoptotic processes. Consequently, this study revealed that computational approach to predict miRNA targets enables the course of narrowing down potential target sites for experimental validation and proves the significance of SNPs on target sites and miRNA geneomic sequences at target sites, especially 5′UTR and CDSs. Highlights: We identified miRSNPs in the CASP3 gene and SNPs in miRNAs genes targeting 5′UTR and coding exons of CASP3. We assessed the impact of these miRSNPs and SNPs of miRNA genes with respect to apoptosis. We found 141 different miRNA binding sites and 6 different SNPs in binding sites, especially in 5′UTR. MiR-339-3p's binding site has a SNP on CASP3 5′UTR and its genomic sequence has a SNP at the same nucleotide. We report a strong association between mi R -339-3p and apoptosis upon computational targeting analysis. Abstract: Apoptosis is described as a mechanism of cell death occurring after adequate cellular harm. Deregulation of apoptosis occurs in many human conditions such as autoimmune disorders, ischemic damage, neurodegenerative diseases and different cancer types. Information relating miRNAs to cancer is increasing. miRNAs can affect development of cancer via many different pathways, including apoptosis. Polymorphisms in miRNA genes or miRNA target sites (miRSNPs) can change miRNA activity. Although polymorphisms in miRNA genes are very uncommon, SNPs in miRNA-binding sites of target genes are quite common. Many researches have revealed that SNPs in miRNA target sites improve or decrease the efficacy of the interaction between miRNAs and their target genes. Our aim was to specify miRSNPs on CASP3 gene (caspase-3) and SNPs in miRNA genes targeting 5′UTR and coding exons of CASP3, and evaluate the effect of these miRSNPs and SNPs of miRNA genes with respect to apoptosis. We detected 141 different miRNA binding sites (126 different miRNAs) and 7 different SNPs in binding sites of miRNA in 5′UTR and CDS of CASP3 gene. Intriguingly, mi R -339-3p's binding site on CASP3 has a SNP (rs35372903, G/A) on CASP3 5′UTR and its genomic sequence has a SNP (rs565188493, G/A) at the same nucleotide with rs35372903. Also, miR-339-3p has two other SNPs (rs373011663, C/T rs72631820, A/G) of which the first is positioned at the binding site. Here, miRSNP (rs35372903) at CASP3 5′UTR and SNP (rs565188493) at miR-339-3p genomic sequence cross-matches at the same site of binding region. Besides, miR-339-3p targets many apoptosis related genes ( ZNF346, TAOK2, PIM2, HIP1, BBC3, TNFRSF25, CLCF1, IHPK2, NOL3) although it had no apoptosis related interaction proven before. This means that miR-339-3p may also have a critical effect on apoptosis via different pathways other than caspase-3. Hence, we can deduce that this is the first study demonstrating a powerful association between miR-339-3p and apoptosis upon computational analysis.